Cultural and nutritional evaluation of the Mexican axolotl (Ambystoma mexicanum): between gastronomic tradition and nutritional value - Huerta Ávila, Gabriela; Chong-Carrillo, Olimpia; Montoya-Martínez, Cynthia Eugenia; Aréchiga-Palomera, Martín A.; Palma-Cancino, David Julián; Vega Villasante, Fernando (Acta Universitaria, 2026)
The Mexican axolotl (Ambystoma mexicanum), a neotenic amphibian endemic to Lake Xochimilco, faces severe threats due to urbanization, pollution, invasive species, and climate change. Historically, it was part of the traditional Mexican diet, but its current gastronomic use is questionable. This study evaluated its importance as a traditional food and its protein contribution to the human diet, analyzing its amino acid profile and comparing it with that of the frog. Results indicate that axolotl meat does not provide a significant nutritional contribution to humans, with protein digestibility-corrected chemical amino acid values ​​below optimal levels. It is concluded that the culinary consumption of the axolotl does not justify its exploitation, given its ecological and cultural importance. It is recommended to implement strict regulations, promote public awareness, and collaborate with conservation initiatives to protect this species and its habitat.